Land and People: Property Investment in Late Pre-Industrial Montréal - Sweeny, Robert; Laing Hogg, Grace (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1995)
Based on a systematic analysis of commutations, this article evaluates the historical significance of new findings on the value of real estate in Montréal in the 1840s. A series constructed from these notarial deeds indicates that property values in all parts of the city were high and that there was a major property cycle over the decade. An estimate of the importance of real estate investment reveals that it would have been substantially more important for both capital accumulation and class formation within the city than international trade. Prior to industrialisation, few popular class families could have afforded the purchase of either a home or a workshop. Property values and housing costs were so high relative to wages, they were a major reason contributing to the high levels of transience among the city's immigrant families and in part explain the rapid development of tenement housing in the wake of the great fire of 1852.